A prospective pilot study of the T‐lymphocyte response to fine particulate matter exposure. Issue 5 (23rd January 2020) - Al Zallouha, Margueritta; Landkocz, Yann; Méausoone, Clémence; Ledoux, Fréderic; Visade, Fabien; Cazier, Fabrice; Martin, Perrine J.; Borgie, Mireille; Vitagliano, Jean‐Jacques; Trémolet, Gauthier; Cailliez, Jean‐Charles; Gosset, Pierre; et al.
Abstract: Exposure to air pollution is associated with increased morbidity and mortality. Once the fine atmospheric particulate matter (FP) is inhaled, some of its compounds can pass through the lungs and reach the bloodstream where they can come into contact with immune cells. Exposure to FP particularly affects sensitive populations such as the elderly. Aging affects the immune system, making the elderly more vulnerable. The project aims to determine the effects of FP exposure on human T cells while looking for biomarkers associated with exposure. Blood samples from 95 healthy subjects in three different age groups (20‐30, 45‐55 and 70‐85 years) were collected to determine a potential age effect. T lymphocytes were isolated to be exposed ex vivo for 72 hours to 45 μg/mL of FP collected in Dunkirk and chemically characterized. Overexpression of the CYP1A1, CYP1B1 and CYP2S1 genes was therefore measured after exposure of the T cells to FP. These genes code for enzymes known to be involved in the metabolic activation of organic compounds such as polycyclic aromatic hydrocarbons detected in the FP sample. T‐cell profiling allowed us to suggest a mixed T‐helper 1/2 profile caused by exposure to FP. With regard to the influence of age, we have observed differences in the expression of certain genes, as well as an increase in interleukin‐4 and ‐13 concentrations in the elderly. These results showed that exposure of T lymphocytes to FP causes effects on both transcriptomic and cytokine secretion levels. Abstract : Fine particulate matter (FP) exposure can lead to health effects particularly in susceptible populations such as the elderly. T lymphocytes isolated from blood of 95 subjects from three age classes were exposed to FP. We noted the induction of CYP1A1, CYP1B1 and CYP2S1 coding for the enzymes involved in the metabolic activation of organic compounds identified in the FP sample as well as a mixed T‐helper 1/2 profile. We also noted differences in the expression of some genes and cytokines with aging.